Natural paint production from anthocyanin extracts of Gerbera jamesonii Bolus ex. Hook F - Taha, R.M.; Hasbullah, N.A.; Rawi, N.; Ramesh, K. (2011)
Gerbera jamesonii (Asteraceae) is a flowering plant with increasing commercial significance. Today, this plant has become one of the leading cut flowers and ranks among the top 10 cut flowers in the world. It is known to contain a high percentage of anthocyanin. Gerbera petals can be a good colourant source and, potentially, a good source of antioxidants. Having potential for producing colourants, the focus of this research thus mainly aimed to extract anthocyanin pigments from fresh G. jamesonii petals and to study the optimum condition for natural paint production from the anthocyanin extracts. Petals from G. jamesonii were collected and dried. Extracts of Gerbera petals were prepared by extracting dried petals using 70 methanol. The extracts were then centrifuged at 5000 rev min(-1) for 15 min, and the supernatant, anthocyanin, was used in the production of natural paint. Polyurethane was used as binder in the paint formulation. Higher concentrations of colourants have shown more stability with the addition of polyurethane in paint systems. The addition of 1 benzoic acid as a co-pigment enhanced the stability of the anthocyanin colour and the quality of the natural paint. In this work, an attempt was made to use natural products in the coating industry.